Knowledge management in sustainable construction projects - Fesenko, T. (ОДАБА, 2022)
The construction project management system provides for the presence of a "solid foundation" of knowledge, which includes technical rules and standards of construction, BIM technologies, and project management standards.The modern development of the construction industry is based on the principles of environmental friendliness, frugality and people-orientation.Turbulent environmental conditions, energy resource limitations become catalysts for the development of knowledge and paradigmatic changes in the management of construction projects.Considering the results of the study―Green reconstruction. Post-war green recovery of Ukraine‖ [1] Ukraine can become a European leader in green transformation thanks to ―green‖ knowledge and solutions in construction.